Utilization of FecJ F gene in developing commercial sheep farming : Economic analysis - Priyanti, Atien; Inonou, I; Tiesnamurti, B (Indonesian Animal Sciences Society, 1996)
An increase of income per capita in Indonesia is not followed by an increase of numbers and quality of lambs stock. To meet he high demand both for domestic and international markets, sheep production should be elaborated commercially . The Research Institute for Animal Production, Bogor has been able to identify the segregation of FecJ F on Javanese sheep, which has large effect on ovulation rate and number of litters born. The study was purposed to analyse the economic value of using Fed gene and the crossing with St. Croix rams to obtain high number of lamb production as well as high pre-weaning growth rate . Sixty seven Garut ewes were used and classified into three classes of singles, twins and triplets or mom: lambs born . From each litter type, ewes were classified according to the breed of rams to be used . Gamt and St . Croix rams were Â used to represent small and large size of sires, respectively . The parameters observed were litter size, birth weight, sex, feed consumption, weaning weight and average daily gain . Lambs and ewes were weighed on biweekly and monthly basis, respectively. An increasing of input for single born ewes was not followed by dramatic increase in its body weight at weaning, which means that the optimum level of production was not achieved. This resulted a shortening of farmers income. However, for ewes having twins an increase of input was followed by significantly increased of production level . Therefore, the economic analysis model used for ewes that carry the Fed gene showed an increase of income of Rp.30,691 .50, and Rp.24,319.82, per ewe per period for St. Croix sires and Garut sires, respectively . Â Key words: Economic analysis, Fed gene, sheep